2012
DOI: 10.1016/j.ejca.2011.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukaemia in the Netherlands: Trends in incidence, treatment and survival, 1989–2008

Abstract: We present trends in incidence, early treatment and survival of Chronic Lymphocytic Leukaemia (CLL) between 1989 and 2008, based on population-based data from the Netherlands Cancer Registry. Incidence rates were stable at 5.1 per 100,000 person-years for males, but increased from 2.3 to 2.5 for females, especially for females aged 50-64 years (from 3.6 to 4.3). Patients were less likely to receive chemotherapy within six months, i.e. from 29% to 24% among males and from 25% to 21% among females. Five-year rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…CLL patients receiving chemotherapy were selected from the PHARMO-ECR cohort. Age and gender of the study patients is similar to descriptions of CLL patients in the literature [3][4][5].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…CLL patients receiving chemotherapy were selected from the PHARMO-ECR cohort. Age and gender of the study patients is similar to descriptions of CLL patients in the literature [3][4][5].…”
Section: Discussionsupporting
confidence: 56%
“…A previous study has shown increased survival rates for CLL patients over the years. Five-year relative survival increased from 61% in 1989-1993 to 70% 2004-2008 for males, and from 71% to 76% for females [5]. The one-year survival rate was slightly higher among patients starting chemotherapy more than 6 months after initial diagnosis than for patients starting chemotherapy within 6 months after initial diagnosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the chances of this are vanishingly small. In an Irish study, myxoma occurred at a rate of 0.5 cases per million people per year [5], while a Dutch study showed that middle aged women developed CLL at a rate of 4 per 100,000 people per year [6]. The cumulative likelihood of developing these as independent processes is, therefore, estimated to be 0.002 per billion people per year.…”
Section: Discussionmentioning
confidence: 99%
“…Also an incidence increase has been observed in a twenty years period in Netherlands among women between 50-64 years old (Van den Broek et al, 2012) and for Denmark between 1943-2003(Thygesen et al, 2009.…”
Section: Introductionmentioning
confidence: 94%